Managing Post COVID-19 Patient with Breathlessness - Yen Shen Wong; Muhammad Amin Ibrahim; Mohd Arif Mohd Zim; Mohd Fauzi Abdul Rani (Case Reports in Medicine)
Background. Chronic respiratory disease may be associated with severity of coronavirus disease 2019 (COVID-19) infection. We review a case of chronic obstructive pulmonary disease (COPD) patient who developed acute breathlessness post COVID-19 infection, also focusing on the diagnostic approach. Case. A 69-year-old gentleman with background history of COPD GOLD D and ischemic heart disease was admitted with severe COVID-19 infection. He required high-flow nasal cannula upon presentation. A computed tomography pulmonary angiography (CTPA) thorax at day 10 of illness revealed moderate organizing pneumonia (OP) with emphysematous changes, without pulmonary embolism. He received oral baricitinib and intravenous methylprednisolone for 3 days, which was then followed by tapering prednisolone starting dose of 1 mg/kg/day (60 mg/day) with reduction of 10 mg prednisolone every 3 days. COPD pharmacotherapy was optimized with early utilization of dual bronchodilators and inhaled corticosteroid was withheld. He underwent inpatient pulmonary rehabilitation and was discharged with home oxygen therapy. Unfortunately, he was re-admitted after 2 weeks with shortness of breath and fever for 3 days. Blood results revealed leucocytosis with raised C-reactive protein. A repeat CTPA showed increase reticulations and crazy paving pattern with reduction in lung volume. Multidisciplinary team discussion concluded it as interstitial pneumonia with COVID-19 OP and fibrosis progression. Prednisolone was stopped and he responded well with antibiotics. A follow-up at 3 months post COVID-19 infection showed improvement of clinical symptoms with radiological resolution of ground glass changes. Conclusion. Corticosteroid inhaler should be cautioned in this case, in view of recent pneumonia and non-elevated serum eosinophil count. These groups of patients should be closely followed up to unmask interstitial lung disease that may present prior to COVID-19 and worsen post-infection. Optimizing pre-existing medical conditions should be the paramount intervention.